Novel Russian guidelines for the assessment and modification of cardiovascular risk in non-cardiac surgery - A. N. Sumin; F. I. Belyalov (Российский кардиологический журнал)
This year, new domestic recommendations for assessing and correcting the risk of cardiac complications during non-cardiac surgery have been published. These guidelines provide simple and practical key messages to facilitate decision-making in real-life clinical practice. The proposed algorithm for the management of patients before non-cardiac operations, focused on integral risk assessment, assessment of functional status and biomarkers. This review provides a summary of perioperative drug therapy, management of the most common CVDs, and focuses on specific care based on the risk of the patient's preexisting clinical conditions. Finally, the document includes practical recommendations for the management of postoperative complications, and also includes a new section on perioperative myocardial infarction/injury.